The Crystal Zero Degree Detector at BESIII as a realistic high rate environment for evaluating PANDA data acquisition modules - Werner, Marcel; Justus Liebig University Giessen (My University, 2015)
The BESIII experiment located in Beijing, China, is investigating physics in the energy region of the charm-quark via electron positron annihilation reactions. A small detector to be placed in the very forward/backward region around theta = 0 degree at BESIII is foreseen to measure photons from the initial state. This is especially interesting, because it opens the door for various physics measurements over a wide range of energies, even below the experiment s designated energy threshold, which is fixed by the accelerator.This thesis is investigating the capabilities of a crystal zero degree detector (cZDD) consisting of PbWO4 crystals placed in that region of BESIII. Detailed Geant4-based simulations have been performed and the energy resolution of the detector has been determined to be sigma/mu = 0.06 + 0.025/sqrt( E[GeV] ).The determination of the center-of-mass energy sqrt(s)_isr after the emission of the photon is of great importance for the study of such events. Preliminary simulations estimated the resolution of the reconstructed sqrt(s)_isr using the cZDD information to be significantly better than 10 % for appropriate photon impacts on the detector. Such events can only be investigated, when data from the cZDD and other detectors of BESIII can be correlated. A fast and powerful Data Acquisition (DAQ) capable of performing event correlation in real time is needed. DAQ modules capable of performing real time event correlation are being developed for the PANDA experiment at the future FAIR facility in Darmstadt, Germany. Investigating these modules in a realistic high-rate environment such as provided at BESIII, offers a great opportunity to gain experience in real time event correlation before the start of PANDA. Developments for the cZDD s DAQ using prototype PANDA DAQ modules have been done and successfully tested in experiments with radioactive sources and a beamtest with 210 MeV electrons at the Mainz Microtron.
Der Crystal Zero Degree Detektor an BESIII als eine realistische Hochraten-Umgebung zur Untersuchung von PANDA Datenaufnahme Modulen
Keywords: cZDD; BESIII; DAQ; PANDA; ISR; cZDD; BESIII; DAQ; PANDA; ISR; ddc:530